Dynamic Coverage Control in Unicycle Multi-Robot Networks Under Anisotropic Sensing - Panagou, Dimitra; Stipanović, Dušan M.; Voulgaris, Petros G. (Frontiers in Robotics and AI, 2015)
This paper considers dynamic coverage control for nonholonomic agents along with collision avoidance guarantees. The novelties of the approach rely on the consideration of anisotropic sensing, which is realized via conic sensing footprints and sensing (coverage) functions for each agent, and on a novel form of avoidance functions. The considered sensing functions encode field-of-view and range constraints, and also the degradation of effective sensing close to the boundaries of the sensing footprint. Thus the proposed approach is suitable for surveillance applications where each agent is assigned with the task to gather enough information, such as video streaming in an obstacle environment. The efficacy of the approach is demonstrated through simulation results.